2014
DOI: 10.1007/s10646-014-1297-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent toxicities of four common chemical pollutants to the marine medaka fish, copepod and rotifer

Abstract: We hypothesize that chemical toxicity to marine ectotherms is the lowest at an optimum temperature (OT) and it exacerbates with increasing or decreasing temperature from the OT. This study aimed to verify this hypothetical temperature-dependent chemical toxicity (TDCT) model through laboratory experiments. Acute toxicity over a range of temperatures was tested on four commonly used chemicals to three marine ectotherms. Our results confirmed that toxicities, in terms of 96-h LC50 (median lethal concentration; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…It was apparent that 28 °C and 31 °C were optimal temperatures for the larvae, whereas control larvae showed less growth and activity at 24 °C. This observation of toxicity being lowest at an optimum temperature with toxicity increasing as the temperature moves away from the optimum temperature has been reported by Li et al for the marine fish Oryzias melastigma . There also may have been changes in the chemistry of Al with increasing temperature, which could have altered the exposure to Al at different temperatures.…”
Section: Resultssupporting
confidence: 80%
“…It was apparent that 28 °C and 31 °C were optimal temperatures for the larvae, whereas control larvae showed less growth and activity at 24 °C. This observation of toxicity being lowest at an optimum temperature with toxicity increasing as the temperature moves away from the optimum temperature has been reported by Li et al for the marine fish Oryzias melastigma . There also may have been changes in the chemistry of Al with increasing temperature, which could have altered the exposure to Al at different temperatures.…”
Section: Resultssupporting
confidence: 80%
“…Focusing on temperature, Martins et al [48] reported that chronic toxicity of the antibiotic florfenicol in Daphnia magna increased as temperature rose (LC50 = 7.6 and 1.9 mg/L at 20 and 25 • C respectively). Li et al [49] concluded that the toxicity of copper, DDT, triphenyltin, and pyrithione to the medaka fish Oryzias melastigma larvae, the copepod Tigriopus japonicus, and the rotifer Brachionus koreanus were temperature-dependent and the LC50 for all four chemicals decreased as the temperature increases. The same effect was observed in other aquatic species when they were exposed to chlorpyrifos and phenol [50].…”
Section: Changes On Enzymatic Activitymentioning
confidence: 99%
“…Unfortunately, there is a lack of information in the literature on this topic, especially about the effects of chronic low-dose chemical exposure combined to other stresses. In fact, several authors have analysed the effects of xenobiotics, and others have reported the effects of their combination with temperature on fish physiology (Hallare et al, 2005;Reynaud and Deschaux, 2006;Li et al, 2014;Andersen et al, 2015;Authman et al, 2015;Guardiola et al, 2015;Olsvik et al, 2016). However, most studies have tested short-term exposure at sub-lethal concentrations which do not reflect actual environmental concentrations of toxicants or the real effects of complex interactions with other stressors such as temperature.…”
Section: Introductionmentioning
confidence: 99%